CUSTOMER JOURNEY MAPPING: UNDERSTANDING CONSUMER BEHAVIOR DIGITALLY - Prasetya Nugraha, Andika; Mulyadi, Mulyadi; Suriani, Suci (CV. Lafadz Jaya, 2024)
In the current digital age, understanding consumer behavior through customer journey mapping has become crucial for companies to provide better and more relevant experiences to their customers. This research aims to explore the concept of customer journey mapping in the digital context and analyze the factors influencing consumer behavior and marketing strategies that can be implemented to enhance the customer experience. Employing a mixed-methods approach combining qualitative and quantitative methods, this research collects data through in-depth interviews, observations, digital data analysis, and surveys. The findings identify the key stages in the digital customer journey and factors such as user experience, trust, personalization, speed, and multi-channel integration that influence consumer behavior. Based on these findings, companies can develop customer-centric marketing and sales strategies, including digital touchpoint optimization, content personalization, multi-channel integration, data-driven marketing, and improved customer service. This research provides valuable insights for business practitioners and academics in understanding digital consumer behavior and optimizing customer experiences in the ever-evolving digital landscape.